Implementation of the Qardh Agreement at Bank Syariah Indonesia Tangerang Branch Office - Musaiyana; Sunaryo Mukhlas, Oyo (Zona Law And Public Administration Indonesia, 2025)
This study aims to determine the implementation of the Qardh contract in financing at Bank Syariah Indonesia Tangerang Branch Office. The Qardh contract is one of the financial instruments in the sharia economic system which aims to provide loans without compensation or additional to meet the needs of the community. This research method involves document analysis, interviews and observations of the implementation process of the Qardh contract at Bank Syariah Indonesia. The results of this study indicate that the institution implements the Qardh contract well and in accordance with the provisions of the DSN fatwa. However, this study also highlights several challenges and improvements that can be applied to increase efficiency and transparency in the implementation of Qardh to strengthen sharia financial inclusion and the challenges faced in its implementation